Effects of Parity and Breastfeeding Duration on Bone Density in Postmenopausal Women - Eun Nam Lee (Elsevier, 2019)
Purpose: This study aimed to identify the effect of parity and breastfeeding duration and the occurrence of lumbar vertebral and femoral neck osteoporosis in Korean postmenopausal women. Methods: This study analyzed the data of 1,770 women based on the 2010-2011 results of the Korea National Health and Nutrition Examination Survey. Extracted data concerning bone density included variables known to be associated with osteoporosis. Complex sample multivariate logistic regression analysis was conducted to determine whether parity and breastfeeding duration were associated with osteoporosis in postmenopausal women. Results: Parity was not associated with postmenopausal osteoporosis in the femoral neck or lumbar vertebrae; however, the risk of femoral neck osteopenia was significantly higher in women with a history of 12-24 months of breastfeeding than in women who breastfed for less than 12 months (odds ratio = 2.12, 95% confidence interval = 1.07-4.21). In women who breastfed for 24 months or longer, the risk of lumbar vertebral osteoporosis was significantly higher than in those who breastfed for less than 12 months (odds ratio = 2.73, 95% confidence interval = 1.18-6.32). Conclusion: Breastfeeding duration may affect the occurrence of lumbar vertebral or femoral neck osteopenia or osteoporosis. Therefore, women who breastfeed for one year or more require education on the risk of bone loss and the need for preventive measures such as adequate calcium intake and physical exercise. Keywords: bone density, breast feeding, parity, osteoporosis, postmenopausal, postmenopause